2020
DOI: 10.1002/cnma.201900597
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Single Atomic Co in CoNx Moieties on Graphene Matrix as an Ultra‐Highly Efficient Active Site for Oxygen Reduction Reaction

Abstract: The sharp increase in current energy consumption needs the development of fuel cells (FCs) as one of sustainable, renewable, efficient and eco-friendly electrochemical conversion systems of energy. The performance of electrocatalysts is crucially important for commercialization of FCs. Commercial Pt based catalysts are used due to their high catalytic activity. However, widespread commercialization is impossible because of the scarcity and poor durability of Pt based catalysts. We are on our quest to find a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…For example, Zhang et al 83 reported that atomically dispersed Ru on N‐doped graphene exhibited higher ORR activity, better durability, and tolerance toward methanol and CO poisoning than commercial Pt/C catalyst in 0.1 mol/L HClO 4 . Shu et al 84 dispersed single‐atom Co species on to sulfuric acid‐treated N‐doped graphene, demonstrating higher durability (94% of the initial current density remained after 7200 seconds operation in 1 mol/L methanol) than that (87% remained) of Pt/C due to the strong covalent bonding between CoN x species and graphene. Mou et al 85 reported that the ORR active sites on atomically dispersed Cu atoms confined in N‐doped graphene are a mixture of Cu‐N 2 and Cu‐N 4 moieties.…”
Section: Graphene‐based Materials For Fuel Cell Applicationsmentioning
confidence: 99%
“…For example, Zhang et al 83 reported that atomically dispersed Ru on N‐doped graphene exhibited higher ORR activity, better durability, and tolerance toward methanol and CO poisoning than commercial Pt/C catalyst in 0.1 mol/L HClO 4 . Shu et al 84 dispersed single‐atom Co species on to sulfuric acid‐treated N‐doped graphene, demonstrating higher durability (94% of the initial current density remained after 7200 seconds operation in 1 mol/L methanol) than that (87% remained) of Pt/C due to the strong covalent bonding between CoN x species and graphene. Mou et al 85 reported that the ORR active sites on atomically dispersed Cu atoms confined in N‐doped graphene are a mixture of Cu‐N 2 and Cu‐N 4 moieties.…”
Section: Graphene‐based Materials For Fuel Cell Applicationsmentioning
confidence: 99%
“…Pyridinic N could reduce electron localization around Co centers, thereby lowering the energy barrier and facilitating the 4e – ORR process (Figure e and f). Shu et al . hydrothermally treated graphene with sulfuric acid to introduce Co ion-exchanging sites (−SH) to prepare highly dispersed single atom Co species catalysts with excellent ORR activity and durability.…”
Section: Typical 4e– Orr Electrocatalystsmentioning
confidence: 99%
“…Pyridinic N could reduce electron localization around Co centers, thereby lowering the energy barrier and facilitating the 4e − ORR process (Figure 6e and f). Shu et al 180 hydrothermally treated graphene with sulfuric acid to introduce Co ion-exchanging sites (−SH) to prepare highly dispersed single atom Co species catalysts with excellent ORR activity and durability. Gao et al 70 designed a novel ZIF using an acetic acid (OAc)-assisted strategy, in which the Co ion had two forms of coordination, one was the known Co-imidazole 182 However, the application of Mn-based catalysts in acidic ORR is limited due to the low metal loadings.…”
mentioning
confidence: 99%